2022
DOI: 10.3390/f13101597
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing Estimation of Forest Aboveground Biomass Based on Lasso-SVR

Abstract: With the Lutou Forest Farm as the research area, the Lasso algorithm was used for characteristic selection, and the optimal combination of variables was input into the support vector regression (SVR) model. The most suitable SVR model was selected to estimate the aboveground biomass of the forest through the comparison of the kernel function and optimal parameters, and the spatial distribution map of the aboveground biomass in the study area was drawn. The significance analysis of special variables showed good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This is in contrast to the studies conducted by other scholars on the correlation between the construction of the aboveground biomass estimation model and the remotely sensed characterization factors or the combination of remotely sensed characterization factors and the point cloud characterization variables. For example, Wang et al [39] extracted vegetation indices based on Sentinel2 image data to construct an aboveground biomass estimation model, and Du et al [40] extracted point cloud feature variables such as canopy cover and leaf area index, as well as texture features such as variance and mean, to construct an aboveground biomass model based on Landsat image data and airborne LiDAR point cloud data; the methodology of this paper has great potential to study the direct correlation between point cloud feature variables and carbon stock.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to the studies conducted by other scholars on the correlation between the construction of the aboveground biomass estimation model and the remotely sensed characterization factors or the combination of remotely sensed characterization factors and the point cloud characterization variables. For example, Wang et al [39] extracted vegetation indices based on Sentinel2 image data to construct an aboveground biomass estimation model, and Du et al [40] extracted point cloud feature variables such as canopy cover and leaf area index, as well as texture features such as variance and mean, to construct an aboveground biomass model based on Landsat image data and airborne LiDAR point cloud data; the methodology of this paper has great potential to study the direct correlation between point cloud feature variables and carbon stock.…”
Section: Discussionmentioning
confidence: 99%
“…The Pearson correlation coefficient is a measure of linear correlation between two variables and is a filter for indirectly assessing regression problems [59]. The closer its value is to 1 (−1), the stronger positive (negative) correlation between the two variables [60].…”
Section: Variable Selection Methodsmentioning
confidence: 99%
“…Accuracy assessment for the spaceborne platform datasets was carried out for datasets, and a regression model on the article's coefficient of determination (R 2 ) was used. Fortyeight (48) articles [10,16,17,63,[65][66][67][68][69][70][71][72][73][74][75][76][78][79][80]82,[84][85][86]88] were employed for further analysis, as they had R 2 values among the total classified articles (54). The error bar plot of R 2 and the regression model used, as shown in Figure 14, showed that the random forest regression model ( 21) was the only model with a reasonable number for analysis, followed by linear regression (5).…”
Section: Spaceborne Analysismentioning
confidence: 99%